Idiopathic Pulmonary Vein Thrombus Extending into Left Atrium: A Case Report and Review of the Literature - Muhammad Asim Rana; Nicholas Tilbury; Yashwant Kumar; Habib Ahmad; Kamal Naser; Ahmed F. Mady; Awani Patel (Case Reports in Medicine)
Pulmonary vein thrombosis (PVT) is rather an uncommon condition which presents nonspecifically and is usually associated with lung malignancy and major pulmonary surgery. Rarely could no cause be found. It causes increased pulmonary venous pressure leading to pulmonary arterial vasoconstriction and subsequent pulmonary arterial hypertension and subsequently can cause cor pulmonale if not addressed in timely fashion. Other associated complications like peripheral embolization and stroke have also been reported. This case emphasizes the importance of maintaining high index of clinical suspicion especially when CT pulmonary angiogram is negative for pulmonary embolism.